Effective shear strength parameters of soil samples taken from slope failure along the KULIM - BALING road / Damanhuri Jamalludin... [et al.] - Jamalludin, Damanhuri; Mohamad Sharom, Nur Syazana; Hashim, Mohamad Zain; Ahmad, Azura; Mohd Nordin, Mohd Mustaqim; Ibrahim, Anas (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Slope failures always occur in Malaysia especially during the monsoon seasons between October and January every year causing fatalities and damages to properties. The main factors causing the slope failure to occur are reduction of the shear strength parameters and loss of negative suction due to saturation of the slope. The objective of this study is to determine the effective shear strength parameters of the soil taken at slope failure using consolidation drain (CD) shear box and also to determine the factor of safety using SLOPE/W software. The soil samples were tested under submerged condition. The minimum value of effective shear strength parameters obtained from the CD shear box tests were c' = 0 kN/m2 and ø' = 47.30 while the maximum value of c' = 30.2 kN/m2 and ø' = 35.6 0. The FOS varied from 0.377 to 0.749 with minimum value of factor of safety was 0.377. When using SLOPE/W software on a stable slope cross section having minimum value of effective shear strength parameters, the minimum value of factor of safety was less than 1 indicating that the slope had already failed.